2018
DOI: 10.1111/irv.12601
|View full text |Cite
|
Sign up to set email alerts
|

The national and provincial burden of medically attended influenza‐associated influenza‐like illness and severe acute respiratory illness in the Democratic Republic of Congo, 2013‐2015

Abstract: BackgroundEstimates of influenza‐associated outpatient consultations and hospitalizations are severely limited in low‐ and middle‐income countries, especially in Africa.MethodsWe conducted active prospective surveillance for influenza‐like illness (ILI) and severe acute respiratory illness (SARI) at 5 healthcare facilities situated in Kinshasa Province during 2013‐2015. We tested upper respiratory tract samples for influenza viruses using a reverse transcription‐polymerase chain reaction assay. We estimated ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
(176 reference statements)
1
23
0
Order By: Relevance
“…Integrated and well-run multi-pathogen surveillance systems, if adequately staffed may provide high quality and timely epidemiological and virological data with a "modest" financial investment. The national burden of illness attributable to specific pathogens can be estimated from sentinel surveillance data through special studies as demonstrated in Zambia and other African countries for influenza [10][11][12][13][14][15][16]. This would be particularly relevant for policy makers if multiple pathogens are included so as to provide the relative burden associated with different etiological agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated and well-run multi-pathogen surveillance systems, if adequately staffed may provide high quality and timely epidemiological and virological data with a "modest" financial investment. The national burden of illness attributable to specific pathogens can be estimated from sentinel surveillance data through special studies as demonstrated in Zambia and other African countries for influenza [10][11][12][13][14][15][16]. This would be particularly relevant for policy makers if multiple pathogens are included so as to provide the relative burden associated with different etiological agents.…”
Section: Discussionmentioning
confidence: 99%
“…Such evaluations are useful to identify shortfalls, improve performance and provide evidence of data reliability for policy making and public health interventions. However, despite recent progress in describing the epidemiology and burden of influenza in sub-Saharan Africa [8][9][10][11][12][13][14][15][16], only a few countries have implemented a comprehensive evaluation of their surveillance systems [17][18][19][20][21].…”
mentioning
confidence: 99%
“…During 2012-2015, the ISSS in DRC performed well with an overall system score of 2.5 (moderate to good performance) on a 3-point scale. In line with its objectives, the utility of the system was demonstrated by its ability to monitor the circulating influenza viruses in the country, monitor the temporal trends of influenza virus circulation, assess the proportional contribution of influenza-associated illness among outpatients and inpatients with ILI or SARI [6], estimate the national burden of influenza-associated illness [13] and contribute to the regional and global understanding of influenza epidemiology, including sharing of clinical samples with WHO collaborating center for annual selection of vaccine strains [5,14,15]. The flexibility of the ISSS in DRC allowed monitoring several syndromes of importance for the country under the same platform, increasing cost-effectiveness and avoiding the implementation of vertical surveillance programs.…”
Section: Discussionmentioning
confidence: 99%
“…During 2012-2015, the ISSS in DRC performed well with an overall system score of 2.6(moderate to good performance) on a 3-point In line with its objectives, the utility of the system was demonstrated by its ability to monitor the circulating influenza viruses in the country, monitor the temporal trends of influenza virus circulation, assess the proportional contribution of influenza-associated illness among outpatients and inpatients with ILI or SARI [6], estimate the national burden of influenza-associated illness [13] and contribute to the regional and global understanding of influenza epidemiology, including sharing of clinical samples with WHO collaborating center for annual selection of vaccine strains [5,14,15].…”
Section: Discussionmentioning
confidence: 90%